Solid state : the story of Abbey Road and the end of the Beatles - Womack, Kenneth (Ithaca [New York] : Cornell University Press, 2019)
"This book examines the creation of the Beatles' final masterwork in terms of the technological strides that made their cumulative achievements possible"--
EMI TG12345 Mk1 -- Stereophonic sound -- Tales of men and Moog -- "The long one" -- The wind-up piano and Mrs. Mills -- Virtuosi et philharmonia -- Tittenhurst Park -- Letting it be -- Solid state.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on September 27, 2019).
Keywords: Beatles; Beatles; Beatles; Abbey Road (Beatles); Rock music -- 1961-1970 -- History and criticism; Rock musicians -- England; Sound recordings -- Production and direction -- England; MUSIC -- History & Criticism; Rock music; Rock musicians; Sound recordings -- Production and direction; England; 1961-1970; Electronic books; Criticism, interpretation, etc